If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -6 = -21 Reorder the terms: -6 + 3n = -21 Solving -6 + 3n = -21 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3n = -21 + 6 Combine like terms: -6 + 6 = 0 0 + 3n = -21 + 6 3n = -21 + 6 Combine like terms: -21 + 6 = -15 3n = -15 Divide each side by '3'. n = -5 Simplifying n = -5
| 9x+29=6x+77 | | 5/6*x-1/5*x+4=7/10*x | | 2x^2+3x^2=144 | | 2a^2+36=18 | | 6=1+4X+x | | -9x+45=x+22.5 | | 18+9d=12d | | 10t+17=-17+12t | | 4x^2-y^2=256 | | 5-x-2y=0 | | -(6y+4)-(5y-7)=1 | | 3b^3+9b=0 | | 121-6x=12x+23 | | 5x+3=7x+-3 | | -6(6y+4)-(-5y-7)=1 | | 3(n+6)=-9 | | 4(7x-1)=3(2x-1)-4(x+6) | | (-2/5)3 | | w^2+16w+64=0 | | 5x+6=106 | | X^2=80X | | 4-3p=-2 | | 10v=60 | | 2(3-w)+6=-6(w-2)-7 | | 0(-8/7) | | X^2=34X | | -6/7w=-42 | | 4x^2-24x=-27 | | -8/15-23/25 | | 1/3(3x-9)=-10+6+3(2-x) | | 6(2x+1)=10x+4 | | 12x-10=10x-6 |